2008
DOI: 10.1121/1.2883744
|View full text |Cite
|
Sign up to set email alerts
|

Effects of in-the-ear microphone directionality on sound direction identification

Abstract: As advanced signal processing algorithms have been proposed to enhance hearing protective device (HPD) performance, it is important to determine how directional microphones might affect the localization ability of users and whether they might cause safety hazards. The effect of in-the-ear microphone directivity was assessed by measuring sound source identification of speech in the horizontal plane. Recordings of speech in quiet and in noise were made with Knowles Electronic Manikin for Acoustic Research wearin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 55 publications
0
22
0
Order By: Relevance
“…The ability to localize can also provide a more natural listening experience (Byrne & Noble 1998). Unfortunately, hearing loss results in a reduction of localization ability (Byrne & Noble 1998), especially for sounds that originate from the back (Köbler & Rosenhall 2002;Chung et al 2008;Keidser et al 2009;Best et al 2010). Hearing aid features that restore the cues for localization are slowly emerging in recent years.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The ability to localize can also provide a more natural listening experience (Byrne & Noble 1998). Unfortunately, hearing loss results in a reduction of localization ability (Byrne & Noble 1998), especially for sounds that originate from the back (Köbler & Rosenhall 2002;Chung et al 2008;Keidser et al 2009;Best et al 2010). Hearing aid features that restore the cues for localization are slowly emerging in recent years.…”
Section: Introductionmentioning
confidence: 97%
“…Likewise, one should also expect a directional microphone to improve front/back localization. Chung et al (2008) examined localization performance of eight normal-hearing and eight hearing-impaired listeners. For both groups, the localization performance with a directional microphone was better than with an omnidirectional microphone.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has failed to control for age and has compared the performance of older hearing impaired listeners to young normal hearing adult listeners (Noble et al, 1994;Van den Bogaert et al, 2006;Chung et al, 2008). Prior work examining neurophysiological responses have suggested that overall responsiveness of the central auditory system and age are correlated (Polich, 2004;Harkrider et al, 2005); consequently, it was reasonable to hypothesize that age may affect localization acuity as part of the aging process in adults.…”
Section: Chapter 6 Discussionmentioning
confidence: 99%
“…Impaired hearing degrades an individual's ability to localize sounds (Hausler, Colburn, & Marr, 1983) and hearing aids often erode performance further. The effects of bilateral hearing aid use have been examined in two main capacities; degree of occlusion and hearing aid technology Noble et al, 1998;Drennan et al, 2005;Keidser et al, 2006;Van den Bogaert et al, 2006;Chung et al, 2008). Extensive research has been done on sound source localization within these areas.…”
Section: Localization Abilitymentioning
confidence: 99%
See 1 more Smart Citation